Implementation and Design of Building Information Modeling (BIM) Oriented Learning in the Building Information and Modeling Design Program (DPIB) - V. Lilik Hariyanto; Indah Wahyuni; Galeh Nur Indriatno Putra Pratama (Jurnal Pendidikan Teknik Sipil, 2025)
Background: BIM is the operational standard for the modern construction industry. This study aims to describe the implementation of Building Information Modeling (BIM) learning in vocational high schools that have a Building Modeling and Information Design program, as well as to formulate a structured Learning Objective Flow in accordance with the principles of the Merdeka Curriculum and the demands of the construction industry. Methods: This study uses a descriptive quantitative approach involving teachers of BIM-related subjects and students in grades X, XI, and XII from SMKN 2 Depok, SMKN 2 Yogyakarta, SMKN 3 Yogyakarta, and SMKN 1 Sedayu. Data were collected through closed-ended questionnaires based on a Likert scale and open-ended questionnaires, then analysed using descriptive statistics to determine trends in each aspect of the study. Results: The results show that the implementation of BIM learning still faces various obstacles, especially in terms of human resources, availability of facilities and infrastructure, curriculum integration, teaching methods, and managerial support. The uneven competence of teachers and the limitations of licensed hardware and software are the main obstacles. Conclusion: This study succeeded in formulating an adaptive, systematic, and contextual learning objective Flow. This flow includes objectives, achievement indicators, learning activities, and assessments that are arranged in stages, starting from mastering basic software skills to developing collaborative projects based on Building Information Modeling (BIM). The findings of this study are expected to provide practical contributions in strengthening the readiness of vocational high schools to implement Building Information Modeling (BIM)-based learning in a focused and sustainable manner.